RegTech Solutions: Generic Business Process Analysis and Modeling - Benny Firmansyah; Arry Akhmad Arman; Widya Sri Wahyuni (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Regulatory Technology, often known as RegTech, is an innovative strategy developed in the finance industry to streamline the regulatory compliance process. RegTech takes advantage of various new technologies such as artificial intelligence (AI), machine learning (ML), big data analytics (BD), cloud computing (CC), robotic process automation (RPA), and various other new technologies. RegTech can be applied to other industries where compliance with and oversight by rules are necessary. To support this, one way to be done is to analyze and model business processes for RegTech solutions in a generic style so that they can be adopted by various other fields in executing these solutions. In this research, a generic business process analysis of RegTech solutions was carried out through a literature study related to the use of RegTech in the financial industry. Next, modeling the analysis results using Business Process Model and Notation (BPMN) with the support of the Bizagi application. The modeling results are then tested for validity and applied to a logical scenario related to non-financial regulatory compliance. The test results show that the business process modeling results are valid and can be used as a reference in implementing RegTech solutions outside the financial sector.